2013
DOI: 10.1097/mnm.0b013e32835fe2e0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of glycosylated hemoglobin (HBA1C) on the extent of perfusion abnormalities and left ventricular dysfunction using gated myocardial perfusion imaging and clinical outcomes in diabetic patients

Abstract: HBA1C is a reliable predictor of coronary artery disease and the magnitude of perfusion defects and LVD and the incidence of NFMIs are higher at an HBA1C level greater than 7.3%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The hs-TnT is an intrinsic myocyte protein, with myocyte turnover associated with its level, reflecting pathophysiological mechanisms, including cardiac cell death, apoptosis, and probably cardiomyocyte strain, and it correlates with CV risk factors, cardiac hypertrophy, and metabolic disorders [49,50]. HbA1c was found to be a predictor of coronary artery disease, left ventricular dysfunction [51,52], and LVH [32]. We confirmed the correlation of HbA1c with LVH in the current study.…”
Section: Clinical and Biochemical Factorssupporting
confidence: 81%
“…The hs-TnT is an intrinsic myocyte protein, with myocyte turnover associated with its level, reflecting pathophysiological mechanisms, including cardiac cell death, apoptosis, and probably cardiomyocyte strain, and it correlates with CV risk factors, cardiac hypertrophy, and metabolic disorders [49,50]. HbA1c was found to be a predictor of coronary artery disease, left ventricular dysfunction [51,52], and LVH [32]. We confirmed the correlation of HbA1c with LVH in the current study.…”
Section: Clinical and Biochemical Factorssupporting
confidence: 81%
“…[ 27 ] Finally, HbA1c levels impact the extent of perfusion abnormalities and left ventricular dysfunction. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have focused on the use of HbA1c levels for the prognosis of patients with diabetes ( 6 , 7 , 9 ). A meta-analysis of four randomized clinical trials ( 10 ), Action to Control Cardiovascular Risk in Diabetes (ACCORD) ( 11 ), Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation (ADVANCE) ( 12 ), the UK Prospective Diabetes Study ( 13 ) and Veterans Affairs Diabetes Trial ( 14 ), found that all-cause and cardiovascular mortality did not increase in the intensive glycemic control group (target glycated hemoglobin ≤6.5%, fasting blood glucose <6.0 mmol/l or absolute HbA1c reduction 1.5%) compared with a non-intensive control group, with a median follow-up period from 3.4–5.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Rocco et al demonstrated that HbA1c was an important predictor of symptomatic hemorrhage following thrombolysis for acute stroke. The results also suggested that hemorrhage following thrombolysis was a consequence of long-term vascular injury rather than of acute hyperglycemia, and that HbA1c may be a more effective predictor than acute blood glucose or a history of diabetes ( 7 ). However, the correlation of low HbA1c levels with coronary artery stenosis and prognosis is not yet clear.…”
Section: Introductionmentioning
confidence: 98%